2015
DOI: 10.1007/s11128-015-1020-2
|View full text |Cite
|
Sign up to set email alerts
|

Continuous-variable quantum key distribution under the local oscillator intensity attack with noiseless linear amplifier

Abstract: An improved continuous-variable quantum key distribution (CVQKD) protocol is proposed to improve the performance of CVQKD system under the local oscillator intensity attack by using a suitable noiseless linear amplifier (NLA) at the destination. This method can enhance the efficiency of the CVQKD scheme in terms of the maximum transmission distance, no matter whether the direct or reverse reconciliation is used. Simulation results show that there is a considerable increase in the transmission distance for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Thanks to the development of experimental techniques, on the other hand, some quantum operations have been used to improve the performance of CVQKD in terms of secret key rate and tolerable excess noise. For example, a heralded noiseless amplifier [26,27,35] was proposed to improve the maximal transmission distance roughly by the equivalent of 20log 10 g dB losses resulting from the compensation of the losses [27]. Recently, due to the fact that the non-Gaussian operation can be used for improving the entanglement [36][37][38] and quan-tum teleportation in CV system [39,40], the photonsubtraction operation, which is one of the non-Gaussian operations, has been proposed to improve the secret key rate, the maximal tolerable excess noise and the transmission distance of CVQKD protocol [11,14,15,29].…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to the development of experimental techniques, on the other hand, some quantum operations have been used to improve the performance of CVQKD in terms of secret key rate and tolerable excess noise. For example, a heralded noiseless amplifier [26,27,35] was proposed to improve the maximal transmission distance roughly by the equivalent of 20log 10 g dB losses resulting from the compensation of the losses [27]. Recently, due to the fact that the non-Gaussian operation can be used for improving the entanglement [36][37][38] and quan-tum teleportation in CV system [39,40], the photonsubtraction operation, which is one of the non-Gaussian operations, has been proposed to improve the secret key rate, the maximal tolerable excess noise and the transmission distance of CVQKD protocol [11,14,15,29].…”
Section: Introductionmentioning
confidence: 99%
“…The improvement of the performance of Gaussian CV-QKD systems using an ideal NLA has been discussed for different protocols and in different scenarios [36][37][38]. However, in all of these works the success probability has been considered based on the theoretical predictions (which is much higher than the actual experimental success probability).…”
Section: Post-selectionmentioning
confidence: 99%
“…Recently, some works have shown that a noiseless linear amplifier (NLA) [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ] could be properly embedded in CV-QKD to fight against channel loss and improve maximum transmission distance [ 37 , 38 , 39 , 40 , 41 ]. In our paper, we consider the use of an NLA inserted before the detection stage in an SR CV-QKD scheme to improve the transmission distance when the reference pulses are weak.…”
Section: Introductionmentioning
confidence: 99%